Meaning Matters: When Does the Quality of Retrieved Contextual Information Influence the Feeling of Knowing?. - Dubois, Stacey. (2017)
Abstract: Research has demonstrated that the amount of accessible information related to an unrecalled target affects feeling-of-knowing (FOK) judgments (Koriat, 1993). In some situations, FOK judgment magnitude is not only related to the amount (quantity) but also the correctness (quality) of retrieved contextual information (e.g. Thomas, Bulevich, & Dubois, 2010). The present study examined the conditions under which the correctness of contextual information influences FOKs. We hypothesized that both quantity and quality of retrieved contextual information would influence FOK judgments in situations where to-be-remembered stimuli were inherently meaningful and where meaningful contextual information was retrieved. In three experiments, we varied meaningfulness of to-be-remembered items both intrinsically and extrinsically. In Experiments 1 (word pairs) and 2 (picture pairs), the quality of retrieved contextual information influenced FOK judgments when semantic attributes were retrieved. However, the quality of retrieved contextual information did not influence mean FOKs when participants encoded inherently meaningless stimuli (Exp. 3).; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Psychology.; Advisor: Ayanna Thomas.; Committee: John Bulevich, and Richard Chechile.; Keywords: Psychology, and Cognitive Psychology.